Prolonged early antenatal indomethacin exposure is safe for fetus and neonate. (17th January 2021) - Turan, Ozhan M.; Driscoll, Colleen; Cetinkaya-Demir, Bilge; Gabbay-Benziv, Rinat; Turan, Sifa; Kopelman, Jerome N.; Harman, Chris
Abstract: Objective: To evaluate fetal and neonatal safety of early-onset long-term antenatal indomethacin treatment (LIT) for short cervix. Methods: In this cohort study, women started LIT for short cervix (<25 mm) before completing 25 weeks. They followed a standardized regiment of oral indomethacin: 100 mg loading, 50 mg qid for 48 h, 25 mg qid until delivery or at 32 weeks gestational age (GA), whichever comes first. Weekly monitoring for oligohydramnios and ductus arteriosus (DA) constriction included confirmation of compliance with treatment/dose. This approach is established in our clinical practice. To identify LIT complications separate from prematurity, each neonate exposed to LIT were matched to two unexposed neonatal controls within ±3 days of GA of delivery and birth weight of ±10%. Odds ratios for neonatal variables included pulmonary hemorrhage, patent DA (PDA) requiring medical or surgical correction, necrotizing enterocolitis (NEC), spontaneous intestinal perforation (SIP), intraventricular hemorrhage (IVH) grade III–IV, other intracranial hemorrhage (ICH), neonatal mortality, calculated individually, and for total composite morbidity. Statistical determinants of neonatal morbidity were assessed using binary logistic regression. Exposure to LIT, maternal age, parity, BMI, GA at delivery, birth-weight (BW), neonatal gender, cord artery pH, and 5-min Apgar score were independent variables. Results: 166 LIT cases were matched with 332 controls. LIT median duration was 49 (3–108) days. Mean delivery GA was 34 weeks. LIT was stopped for 5 patients (2.9%) with oligohydramnios and 1 (0.6%) with DA constriction, without consequent morbidity. 71 cases (43%) completed LIT, stopping at 32 weeks. 95 stopped early for preterm premature ruptures of membranes (PPROM) (20%), active labor (11%) or patient choice (22%). Odds of any individual complication did not differ between treated cases and controls. LIT was not a statistical determinant of composite morbidity or any individual neonatal problem. Conclusion: Continuous early-onset indomethacin exposure, up to 15 weeks antenatally, did not increase fetal or neonatal complications. This level of safety is permissive to a randomized trial of indomethacin for the treatment of short cervix.